2006
DOI: 10.1207/s15327027hc1901_1
|View full text |Cite
|
Sign up to set email alerts
|

Social Distance, Perceived Drinking by Peers, and Alcohol Use by College Students

Abstract: Many colleges in the United States are employing social norms marketing campaigns with the goal of reducing college students' alcohol use by correcting misperceptions about their peers' alcohol use. Although the typical message used in these campaigns describes the quantity and frequency of alcohol use by the average student on campus, many students may find such a vague comparison to others to be socially irrelevant. This study compares the relative weight of perceptions about alcohol use by distant versus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 32 publications
7
65
1
Order By: Relevance
“…Two-Part Model of Monthly Alcohol Consumption (numbers in parenthesis are for the sample excluding alcohol-dependent students) are not predictive of alcohol consumption . Other studies have reported that proximal peers, such as friends, appear to be stronger predictors of drinking behavior than more distal peers, such as peer students (Yanovitzky et al, 2006). Indeed, in our study, while perceived approval of HED by friends is in association with both the probability of engaging in HED and HED frequency, perceived prevalence of HED among peer students is only associated with HED frequency.…”
Section: The Influence Of Social Normscontrasting
confidence: 44%
See 1 more Smart Citation
“…Two-Part Model of Monthly Alcohol Consumption (numbers in parenthesis are for the sample excluding alcohol-dependent students) are not predictive of alcohol consumption . Other studies have reported that proximal peers, such as friends, appear to be stronger predictors of drinking behavior than more distal peers, such as peer students (Yanovitzky et al, 2006). Indeed, in our study, while perceived approval of HED by friends is in association with both the probability of engaging in HED and HED frequency, perceived prevalence of HED among peer students is only associated with HED frequency.…”
Section: The Influence Of Social Normscontrasting
confidence: 44%
“…This variable was not retained in any of the models explaining alcohol use. University norms are related to more distal referents than are peer students and friends and proximal peers are more likely to affect behavior (Yanovitzky et al, 2006). Furthermore, while French universities all enforce anti-smoking policies, alcohol policies mostly do not exist.…”
Section: The Influence Of Social Normsmentioning
confidence: 99%
“…This is consistent with social identity theory (Terry and Hogg, 1996) and reference group theory (Hyman and Singer, 1968), both of which posit that proximal peers (ingroup) are more likely to be a signifi cant reference group than more distal groups (outgroup) and hence will more strongly infl uence attitudes and behaviors because of greater value placed on the ingroup. Indeed, for both injunctive and descriptive norms, literature supports a stronger prediction by close friends' norms compared with the norms of more distal peer groups (Cho, 2006;Park et al, 2009;Urberg et al, 1997;Yanovitzky et al, 2006). However, fi ndings are suggestive that the relative infl uence of descriptive versus injunctive norms may vary as a function of referent Phua, 2013).…”
Section: Social Normative Infl Uencesmentioning
confidence: 96%
“…For example, peer use and perceptions of social approval may effect change for both smoking and alcohol use (Andrews, Tildesley, Hops, & Fuzhong, 2002;Moran et al, 2004;Myers & MacPherson, 2008;Yanovitzky, Stewart, & Lederman, 2006). Additionally, individual level variables may differentially predict transitions for those at lower levels of use than those for whom smoking and drinking is more established (Wetter et al, 2004).…”
Section: Examining the Stability Of Alcohol Tobacco Co-use -16mentioning
confidence: 99%